STRUCTURAL AND MAGNETIC CHARACTERIZATION OF Fe₃O₄ NANOPARTICLES SYNTHESIZED AT ROOM TEMPERATURE - SOUCA, G.; MICAN, S.; STEFANCU, A.; CHIŞ, V.; TETEAN, R.; LEOPOLD, N. (Studia Universitatis Babeș-Bolyai Physica, 2016)
Magnetite nanoparticles without surfactants were obtained by room temperature synthesis. X-ray diffraction data show that the nanoparticles crystallize in a cubic single phase structure. An average crystallite size of around 24 nm was calculated. The obtained Fe3O4 nanoparticles are ferrimagnetic at 4 K and at 300 K, too. It was shown that a ferrimagnetic to superparamagnetic transition is present, even if the superparamagnetic state is not pure. We assume that the true long-range ferromagnetic coupling is absent due to the small grain size of the sample.